A matched-pair analysis comparing stereotactic radiosurgery with whole-brain radiotherapy for patients with multiple brain metastases - El-Shafie, Rami; Celik, Aylin; Kronsteiner, Dorothea; Schmitt, Daniela; Uzun-Lang, Kristin; König, Laila; Bernhardt, Denise; Höne, Simon; Forster, Tobias; Nettelbladt, Bastian von; Adeberg, Sebastian; Debus, Jürgen; et al. (Journal of neuro-oncology, 2020)
Stereotactic radiosurgery (SRS) is an emerging treatment for patients with multiple brain metastases (BM). The present work compares the SRS of multiple brain metastases with whole-brain radiotherapy (WBRT).